Effect of Head Elevation to Different Heights in Laryngeal Exposure with Direct Laryngoscopy - Acharya, Pragya; Shrestha, Anil; Gurung, Arjun; Koirala, Megha; Shrestha, Gentle Sundar; Marhatta, Moda Nath (Journal of Nepal Health Research Council, 2019)
Background: The purpose of this study was to determine the optimal pillow height for the best laryngoscopic view in adult patients scheduled for elective surgery under general anaesthesia. Methods: 150 adult patients undergoing surgery under general anaesthesia with endotracheal intubation with no features suggestive of difficult airway were enrolled for the study. After induction of anaesthesia the assessment of direct laryngoscopic views was done at head positions without a pillow and with non-compressible pillows of heights 5cm and 10cm. Results: The laryngoscopic view with the 5cm pillow was significantly superior to other head position (p<0.01). The incidence of difficult laryngoscopy (Cormack and Lehane grade III) was 32.7% without a pillow which improved to (Cormack and Lehane grade III) 4% with 10cm pillow and there were no cases of difficult laryngoscopy with 5cm pillow. Conclusions: The use of 5cm pillow in the ‘sniffing’ position obtains the best laryngoscopic view during direct laryngoscopy. Keywords: Direct laryngoscopy; head elevation; laryngoscopicview; pillow height.